2010
DOI: 10.1590/s0021-75572010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Notificação imprecisa da ingestão energética na dieta de adolescentes

Abstract: The results obtained demonstrated a high percentage of misreporting of energy intake among adolescents, especially among obese subjects, which suggests that energy-adjusted nutrient intake values should be employed in diet-disease risk analysis in order to contribute to a reduction in errors associated with misreporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
2
2
0
3
Order By: Relevance
“…e prevalence of misreporting in the present study was 72.6%. Our nding is also consistent with the results of Vainik et al [29] and Santos et al [30], which showed prevalence of 66% and 74% of misreporting in adolescents, respectively. erefore, the dietary data of the current work were energy-adjusted using the residual method, which is considered an appropriate tool to decrease the in uence of misreporting in studies based on food records [31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…e prevalence of misreporting in the present study was 72.6%. Our nding is also consistent with the results of Vainik et al [29] and Santos et al [30], which showed prevalence of 66% and 74% of misreporting in adolescents, respectively. erefore, the dietary data of the current work were energy-adjusted using the residual method, which is considered an appropriate tool to decrease the in uence of misreporting in studies based on food records [31].…”
Section: Discussionsupporting
confidence: 93%
“…Categorical data were presented using absolute and relative prevalence. Due to underreporting, which is a common issue in the dietary assessment of adolescents [29,30], data were energy-adjusted using the residual method. is approach was suggested by Poslusna et al [31] as an alternative to handle misreporting, since exclusion of underreporters is not recommended [31,32].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Energy intakes are often overestimated with FFQs compared to 24HR (which was found in this study, manuscript in preparation). Since under and over reporting in food intake studies are well known, participants who reported consuming less than 0.79 or above 2.4 times their basal metabolic rate calculated using Schofield formula were therefore excluded from diet‐related analysis . Eighty‐five participants in 2013 and 84 in 2014 were included to generate the aggregated FFQ food intake results .…”
Section: Methodsmentioning
confidence: 99%
“…O mesmo foi observado em um estudo conduzido com adolescentes, com idades entre 14 e 19 anos, matriculados em escolas estaduais de Ribeirão Preto 23 . Estudo realizado com adolescentes com idade média de 16 anos constatou que adolescentes obesos tem 5 vezes mais chances de subnotificar a ingestão energética do que adolescentes com peso normal 24 . O cálcio, relevante durante a adolescência por contribuir para a mineralização óssea 25 , destacou-se em decorrência do consumo insuficiente por parcela substancial de adolescentes (55%) desta pesquisa.…”
Section: Discussionunclassified